Quantification of carotid plaque composition with a multi-contrast atherosclerosis characterization (MATCH) MRI sequence - Kassem, Mohamed; Nies, Kelly P. H.; Boswijk, Ellen; van der Pol, Jochem; Aizaz, Mueez; Gijbels, Marion J. J.; Li, Debiao; Bucerius, Jan; Mess, Werner H.; Wildberger, Joachim E.; van Oostenbrugge, Robert J.; Moonen, Rik P. M.; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background and purpose: Carotid atherosclerotic plaques with a large lipid-rich necrotic core (LRNC), intraplaque hemorrhage (IPH), and a thin or ruptured fibrous cap are associated with an increased stroke risk. Multi-sequence MRI can be used to quantify carotid atherosclerotic plaque composition. Yet, its clinical implementation is hampered by long scan times and image misregistration. Multi-contrast Atherosclerosis Characterization (MATCH) overcomes these limitations. The main objective was to compare quantification of plaque composition with MATCH and multisequence MRI.Methods: MATCH and multi-sequence MRI were used to image 54 carotid arteries of 27 symptomatic patients with ≥2mm carotid plaque on a 3.0 Tesla MRI scanner. The following sequence parameters for MATCH were used: repetition time/echo time (TR/TE): 10.1/4.35 msec, field of view (FOV): 160x160x2 mm, matrix size: 256x256, acquired in-plane resolution: 0.63x0.63 mm², number of slices: 18, and flip angles: 8°,5°,10°. Multi-sequence MRI (black blood pre-and post-contrast T1w, time of flight, and magnetization prepared rapid acquisition gradient echo; acquired in-plane resolution: 0.63x0.63 mm²) was acquired according to consensus recommendations. Image quality was scored (5-point scale). The interobserver agreement in plaque composition quantification was assessed by intraclass correlation coefficient (ICC). The sensitivity and specificity of MATCH in identifying plaque composition were calculated using multi-sequence MRI as a reference standard.Results: A significantly lower image quality of MATCH compared to multi-sequence MRI was observed (p<0.05). The Scan time for MATCH was shorter (7 vs 40 minutes). Interobserver agreement in quantifying plaque composition on MATCH images was good-to-excellent (ICC≥0.77) except for total volume of calcifications and fibrous tissue that showed moderate agreement (ICC≥0.61). The sensitivity and specificity of detecting plaque components on MATCH were ≥89% and ≥91% for IPH, ≥81% and 85% for LRNC, and ≥71% and ≥32% for calcifications. Overall, goodto-excellent agreement (ICC≥0.76) of quantifying plaque components on MATCH with multisequence MRI as reference standard was observed except calcifications (ICC=0.37-0.38), and fibrous tissue (ICC=0.59-0.70).MATCH images can be used to quantify plaque components such as LRNC and IPH but not for calcifications. Although MATCH images showed a lower mean image quality score, short scan time and inherent co-registration are significant advantages.